Produção de enzimas ligninolíticas e proteômica de Marasmiellus palmivorus VE111: aplicação do secretoma em processos de grafting enzimático e etanol de segunda geração - Schneider, Willian Daniel Hahn (My University, 2019)
Species of the genus Marasmiellus, a white-rot fungi, have potential in the degradation of lignocellulose, especially lignin. In the present work, it was study the production of ligninolytic enzymes by Marasmiellus palmivorus VE111 in a bioreactor with mechanical agitation, evaluating the influence of different sources of carbon, nitrogen and inductors on the production of these enzymes, as well as other cultivation parameters such as pH, temperature and concentration of dissolved oxygen. Subsequently, under optimized production conditions, a proteomic study of the enzyme broth was applied in the production of second-generation ethanol and enzymatic grafting technology, i.e. in the formation of covalent bonds of a target compound on a desired substrate, by an enzyme-based reaction. Under optimized conditions, it was verified the production of 6588 U/mL of laccases, 3533 U/mL of total peroxidases and 60 U/mL of manganese peroxidases by M. palmivorus VE111, using 5 g/L glucose, 1.80 g/L casein, 3 mmol/L CuSO4 and MnSO4, 90% concentration of dissolved oxygen, at 28 °C, initial free pH up to 48 h of cultivation and pH fixed at 7.0 to 120 h. Under these conditions, maximum mycelial growth of 6.8 g/L, laccase volumetric productivity of 58.35 U/mL/h and a biomass volumetric productivity of 0.073 g/L/h was verified. Optimum reaction pH values of laccase activity were found in sodium citrate buffer, pH 3.5, and total peroxidases in Mc'Ilvaine buffer pH 3.0. The optimum reaction temperature for laccases was 40 °C and for total peroxidases, 25 °C. Four laccase isoforms were identified on the native gel of activity. The secretome of M. palmivorus VE111 contains 21% glycosyl hydrolases and 18% oxidoreductases. Among the oxidoreductases, the majority corresponds to laccases (45%). Peroxidases were identified in a lower proportion (12%). It was verified a delignification of Eucalyptus globulus in natura (31% reduction in lignin) and detoxification of E. globulus pretreated by steam explosion with the M. palmivorus VE111 enzyme broth, resulting in increases in ethanol yield for both biomass, of 5% and 10%, respectively, after enzymatic saccharification. In addition, the laccases of M. palmivorus VE111 catalyze reactions of polymerized phenolic aromatic compounds on the wood surface of E. globulus, providing greater hydrophobicity to the material. Considering the above, the laccases of M. palmivorus VE111 act in the polymerization and depolymerization of aromatic and phenolic substances, being applicable in technologies of enzymatic grafting and econd-generation ethanol, respectively.
spécies do gênero Marasmiellus, fungos de degradação branca, apresentam potencial na degradação da lignocelulose, especialmente da lignina. No presente trabalho, estudou-se a produção de enzimas ligninolíticas por Marasmiellus palmivorus VE111, em biorreator com agitação mecânica, avaliando a influência de diferentes fontes de carbono, nitrogênio e indutores na produção dessas enzimas, bem como de demais parâmetros de cultivo como pH, temperatura e concentração de oxigênio dissolvido. Posteriormente, sob condições de produção otimizadas, um estudo proteômico do caldo enzimático foi aplicado na produção de etanol de segunda geração e na tecnologia de grafting enzimático, isto é, na formação de ligações covalentes de um composto alvo em um substrato desejado, por meio de uma reação enzimática. Nas condições otimizadas, verificou-se a produção de 6588 U/mL de lacases, 3533 U/mL de peroxidases totais e 60 U/mL de manganês peroxidases por M. palmivorus VE111, utilizando 5 g/L de glicose, 1,80 g/L de caseína, 3 mmol/L de CuSO4 e MnSO4, concentração de oxigênio dissolvido fixa em 90%, a 28 ºC, pH inicial livre até 48 h de cultivo e pH fixo em 7,0 até 120 h. Nessas condições, verificou-se crescimento micelial máximo de 6,8 g/L, produtividade volumétrica de lacases de 58,35 U/mL/h e produtividade volumétrica de biomassa de 0,073 g/L/h. Valor de pH ótimo de reação de atividade de lacases foi identificado em tampão citrato de sódio, pH 3,5, e de peroxidases totais em tampão Mc’Ilvaine, pH 3,0. A temperatura ótima de reação para lacases foi 40 ºC e para peroxidases totais, 25 ºC. Foram identificadas quatro isoformas de lacases em gel nativo de atividade. O secretoma de M. palmivorus VE111 contém 21% de glicosil hidrolases e 18% de oxidoredutases. Entre as oxidoredutases, a maior parte corresponde às lacases (45%). Peroxidases foram identificadas em menor proporção (12%). Verificou-se uma deslignificação de Eucalyptus globulus in natura (31% de redução na lignina) e detoxificação de E. globulus pré-tratado por explosão a vapor com o caldo enzimático de M. palmivorus VE111, resultando em incrementos no rendimento em etanol para ambas as biomassas, de 8,5% e 10%, respectivamente, após sacarificação enzimática. Outrossim, as lacases de M. palmivorus VE111 catalisam reações de polimerização de compostos aromáticos fenólicos sobre a superfície de madeira de E. globulus, proporcionando maior hidrofobicidade ao material. Diante do exposto, as lacases de M. palmivorus VE111 agem na polimerização e despolimerização de substâncias aromáticas e fenólicas, sendo aplicáveis em tecnologias de grafting enzimático e etanol de segunda geração, respectivamente.
Keywords: Enzimas de fungos; Álcool; Biocombustíveis; Biotecnologia; Fungal enzymes; Alcohol; Biomass energy; Biotechnology